The Effect of the Fibrinogen Concentration and the Leukocyte Count on Intravascular Fibrin Deposition from Soluble Fibrin Monomer Complexes - Gurewich, Victor; Lipinski, Boguslaw; Hyde, Elisabeth (Thrombosis and Haemostasis, 1976)
Fibrin formation from fibrin monomer (FM) complexes was studied in experimental animals utilizing a previously described technique for quantitating fibrin deposition. A uniform thrombin infusion was used to produce FM, fibrinolysis being inhibited by EACA. In vivo complex formation between FM and 125I-fibrinogen was demonstrated chromatographically. A direct correlation was found between blood fibrinogen concentration and fibrin deposition in organs. By contrast, an inverse correlation between fibrinogen concentration and both enzymatic or non-enzymatic fibrin formation was found in vitro. The mechanism by which fibrinogen potentiates FM precipitation in vivo could not be explained by coprecipitation of fibrinogen in the complex which could not be demonstrated. The inhibitory effect of HN2 on fibrin deposition despite the associated hyperfibrinogemia induced by this drug is believed to underscore the importance of leukocytes in certain types of fibrin deposition. A correlation between the leukocyte count and fibrin formation from FM was also found. It was concluded that the risk of intravascular fibrin deposition is increased by a raised fibrinogen level especially when accompanied by leukocytosis.